Pengaruh Hedonic Shopping Motivation dan Sales Promotion Terhadap Impulse Buying Pada Konsumen E-Commerce Shoppe - Arti, Ni Luh Yuni; Hartati, Putu Sri; Astrama, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of hedonic shopping motivation and sales promotion partially and simultaneously on impulse buying. The research location is in Tabanan, Bali. The sample used was 120 respondents. The data analysis technique used is Multiple Linear Regression. 4.291 and sig 0.000. (2) sales promotion has a significant positive effect on impulse buying, where the t value is 5.324 and sig 0.000. (3) Simultaneously hedonic shopping motivation and sales promotion have a significant effect on impulse buying, where the F value is 63,492 and the significance is 0,000. The magnitude of the influence of the independent variable on impulse buying is 52.0%. The suggestion in this research is that E-Commerce Shoppe is expected to increase the variety of products sold and add features available at E-Commerce Shoppe and always provide a guarantee on all products sold